2019
DOI: 10.1063/1.5079832
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of thermal conductivity and specific heat by impedance spectroscopy of Bi2Te3 thermoelectric element

Abstract: The thermal conductivity (κ) and specific heat (Cp) of a thermoelectric element consisting of Bi2Te3 (SRM 3451) were obtained by impedance spectroscopy and using only electrometric measurements. The dimensionless figure of merit (zT) was successfully estimated by the four-probe method from the frequency dependence of the impedance, and the result was compared with that obtained using the two-probe method. The calculated values of zT and resistivity were 0.577 and 13.4 µΩ m, respectively, at 300 K, which allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The zT is calculated as a result of measuring each of the parameters, S, ρ, and κ. 1) Additionally, impedance spectroscopy has been introduced to determine the zT of merit directly from the frequency dependence of the impedance Z(ω) as follows: [5][6][7][8][9][10][11][12] where ΔT is the temperature difference along the length of the sample in the frequency domain, I is the alternating current, R ohm and R TE are the ohmic resistance and impedance derived from the thermoelectric effect, respectively, K is the thermal conductance, A and L are the cross-section and length of each thermoelectric element, respectively, and ω TE is the characteristic angular frequency proportional to α/L 2 , where α is the thermal diffusivity. Further, this technique has the advantage of estimating the κ without controlling the heat flux using the thermoelectric material after measuring the Seebeck coefficient from the definition of the zT:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The zT is calculated as a result of measuring each of the parameters, S, ρ, and κ. 1) Additionally, impedance spectroscopy has been introduced to determine the zT of merit directly from the frequency dependence of the impedance Z(ω) as follows: [5][6][7][8][9][10][11][12] where ΔT is the temperature difference along the length of the sample in the frequency domain, I is the alternating current, R ohm and R TE are the ohmic resistance and impedance derived from the thermoelectric effect, respectively, K is the thermal conductance, A and L are the cross-section and length of each thermoelectric element, respectively, and ω TE is the characteristic angular frequency proportional to α/L 2 , where α is the thermal diffusivity. Further, this technique has the advantage of estimating the κ without controlling the heat flux using the thermoelectric material after measuring the Seebeck coefficient from the definition of the zT:…”
mentioning
confidence: 99%
“…Several authors have reported different models and experimental techniques to evaluate the zT using materials that exhibit high zT values such as bismuth telluride, which has zT ∼ 1. [5][6][7][8][9][10][11][12] On the other hand, impedance spectroscopy can be applied to assess the thermoelectric parameters of materials with significantly low values of the zT. Therefore, in this study, we investigated the feasibility of employing impedance spectroscopy for estimating thermoelectric parameters using constantan, which has a larger S compared to metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that the effective thermal conductivity of Bi 2 Te 3 /MASnI 3 asymptotically approaches 0.17 W/(m·K) at a film thickness sufficiently larger than 1 µm. This value is calculated from the experimental values of Bi 2 Te 3 and MASnI 3 : 2.11 W/(m·K) 62 and 0.09 W/(m·K) 41 , respectively. This upper limit does not depend on the interfacial thermal conductance because the influence of the interface is negligible in the limit of large D. In contrast, when the film thickness is sufficiently smaller than 1 µm, the interfacial thermal conductance significantly influences the effective thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, phonon MFP of the Bi 2 Te 3 film was estimated using the group velocity and lattice thermal conductivity presented in Tables I and II while specific heat C was used with a literature value of 165 J (kg −1 •K −1 ). 28) Thus, the phonon MFP of the Bi 2 Te 3 film was determined to be 0.49 nm, which was 35% of the value for the singlecrystal. In addition, the phonon MFP of the Bi 2 Te 3 film was 14% for the grain size, indicating that the phonons were scattered inside the grains at point defects such as atomic vacancies and grain boundaries.…”
mentioning
confidence: 87%